Positive electrode material, method for preparing the same, and electrochemical device

By doping Sr elements into nickel-cobalt-manganese ternary cathode materials and forming multilayer coatings of Ce, Nb, and W, the problem of poor power performance of high-voltage ternary cathode materials under low-temperature conditions is solved. Stable lithium-ion transport and interface stability of the material under high voltage and low temperature are achieved, thereby improving the overall performance of the electrochemical device.

CN123033962APending Publication Date: 2026-11-03NANTONG RESHINE NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611249080.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

High-voltage ternary cathode materials exhibit poor power performance at low temperatures. The lithium-ion diffusion coefficient decreases, the electrolyte viscosity increases, leading to a decrease in ion migration rate, exacerbating interfacial side reactions, dissolving transition metals, excessive CEI film growth, increasing interfacial impedance, and the increased nickel content results in more residual lithium compounds on the surface. These factors accelerate capacity decay and increase impedance.

Method used

By doping Sr into the nickel-cobalt-manganese ternary precursor, a multilayer coating containing Ce, Nb, and W is formed, which optimizes the lithium-ion migration channel, improves bulk diffusion and interface stability, reduces interface impedance, and enhances structural stability.

Benefits of technology

Under high voltage and low temperature conditions, the lithium-ion transport efficiency and interfacial charge transfer efficiency of the cathode material are improved, the interfacial impedance is reduced, the structural stability is enhanced, and the power performance and cycle stability are improved, especially maintaining good power performance at -10℃.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123033962A_ABST
    Figure CN123033962A_ABST
Patent Text Reader

Abstract

The application provides a positive electrode material, a preparation method thereof and an electrochemical device. The method comprises the following steps: mixing a nickel-cobalt-manganese ternary precursor, a dispersing agent and a solvent to obtain a mixture; mixing the mixture, a lithium salt, an Sr element and a doping element, and performing primary sintering in an oxygen atmosphere to obtain a base body doped with the doping element; mixing the base body and a first coating material, and performing secondary sintering in an oxygen atmosphere, so that the first coating material is coated on the surface of the base body to obtain a base body with a first coating layer, and the first coating material comprises a Ce element; mixing the base body with the first coating layer and a second coating material, and performing tertiary sintering in an air atmosphere, so that the second coating material is coated on the surface of the first coating layer to form a second coating layer, and the second coating material comprises an Nb element and a W element. The positive electrode material provided by the application can maintain good power performance under high-voltage and low-temperature conditions through the synergistic effect of Sr phase doping and multi-layer coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of new energy technology, and in particular to a cathode material, its preparation method and electrochemical device. Background Technology

[0002] With the rapid development of new energy vehicles and power tools, the requirements for energy density and power performance of lithium-ion batteries are increasing. High-voltage ternary cathode materials have become a research hotspot due to their energy density advantage, but the power performance degradation of high-voltage ternary cathode materials under low-temperature conditions is particularly prominent.

[0003] In low-temperature environments, the lithium-ion diffusion coefficient within the cathode material decreases, and the increased electrolyte viscosity leads to a reduced ion migration rate and increased battery internal resistance. To compensate for insufficient energy output at low temperatures, existing methods generally increase the charging cut-off voltage. However, when the voltage exceeds 4.45V, interfacial side reactions between the cathode and electrolyte intensify, leading to transition metal dissolution, excessive CEI film growth, and increased interfacial impedance. Therefore, low temperatures limit bulk lithium-ion diffusion, while high voltage exacerbates interfacial side reactions; the combined effect increases charge transfer impedance and degrades power performance. Simultaneously, increased nickel content leads to more residual lithium compounds on the surface, which readily trigger more side reactions, accelerating capacity decay and increasing impedance. Summary of the Invention

[0004] In view of this, in order to solve at least one of the above technical problems, this application provides a method for preparing a cathode material.

[0005] In addition, this application also provides a cathode material prepared by the aforementioned preparation method and the application of the cathode material.

[0006] In a first aspect, this application provides a method for preparing a cathode material, comprising: mixing a nickel-cobalt-manganese ternary precursor with a lithium salt and a dopant, and sintering it once in an oxygen atmosphere to obtain an element-doped matrix, wherein the dopant element in the dopant material includes at least Sr; mixing the matrix with a first coating material, and sintering it a second time in an oxygen atmosphere to form a first coating layer on the surface of the matrix, thereby obtaining a primary coating product, wherein the first coating material includes Ce; and mixing the primary coating product with a second coating material, and sintering it a third time in an air atmosphere to form a second coating layer on the surface of the first coating layer, thereby obtaining the cathode material, wherein the second coating material includes Nb and W.

[0007] Based on the first aspect, in some embodiments of this application, in the step of mixing the nickel-cobalt-manganese ternary precursor, lithium salt and dopant, the amount of Sr added is 0.01%~0.05% based on the mass of the nickel-cobalt-manganese ternary precursor; and / or, when mixing the matrix with the first coating material, the amount of Ce added is 0.01%-0.05% based on the mass of the matrix.

[0008] Based on the first aspect, in some embodiments of this application, the temperature of the first sintering is 800℃-900℃, the time is 8h~10h, the matrix is ​​a single crystal particle, and the particle size of the matrix is ​​1μm~2μm.

[0009] Based on the first aspect, in some embodiments of this application, before the step of mixing the nickel-cobalt-manganese ternary precursor with lithium salt and dopant, the method further includes: pretreating the nickel-cobalt-manganese ternary precursor, the pretreating step including: mixing the untreated nickel-cobalt-manganese ternary precursor, dispersant and solvent to obtain a mixture; spray drying the mixture at 80℃-100℃ for 2h-4h to obtain a dried precursor; and pre-sintering the dried precursor at a temperature of 400℃-600℃ for 3h-5h.

[0010] Based on the first aspect, in some embodiments of this application, in the step of mixing the nickel-cobalt-manganese ternary precursor, lithium salt and dopant material, the amount of dopant elements other than Sr added to the dopant material is 0.05% to 0.1%, based on the mass of the nickel-cobalt-manganese ternary precursor.

[0011] Based on the first aspect, in some embodiments of this application, the doping elements further include Ti and W elements.

[0012] Based on the first aspect, in some embodiments of this application, the amount of Ti added is 0.05% to 0.1% based on the mass of the nickel-cobalt-manganese ternary precursor; and the amount of W added is 0.1% to 0.3% based on the mass of the nickel-cobalt-manganese ternary precursor.

[0013] Based on the first aspect, in some embodiments of this application, the temperature of the secondary sintering is 600℃~700℃ and the time is 5h~8h; and / or, the temperature of the tertiary sintering is 400℃-600℃ and the time is 4h-6h.

[0014] Secondly, this application provides a cathode material, which is prepared by the preparation method described above.

[0015] Thirdly, this application provides an electrochemical device, including a positive electrode, a negative electrode, and an electrolyte disposed between the positive electrode and the negative electrode, wherein the positive electrode includes the aforementioned positive electrode material.

[0016] The cathode material preparation method provided in this application introduces Sr element into the matrix for bulk doping. Sr doping can cause changes in lattice parameters, optimizing the migration channels of lithium ions in the matrix, thereby helping to improve the diffusion kinetics of lithium ions in the bulk phase under low-temperature conditions. A first coating layer containing Ce element and a second coating layer containing Nb and W element are sequentially formed on the matrix surface. The Ce element coating layer can chemically stabilize the matrix surface, reduce side reactions between residual lithium compounds on the surface and the electrolyte, control the growth of the CEI film, and reduce the interfacial impedance, thereby helping to improve the impedance growth problem caused by the aggravation of interfacial side reactions under high voltage conditions. Nb and W elements further modify the surface of the first coating layer, thereby enhancing the structural stability of the first coating layer. Through the synergistic effect of Sr element bulk doping and Ce, Nb, and W element surface coating, this application improves both the bulk lithium ion transport efficiency and interfacial charge transfer efficiency of the cathode material, thus simultaneously achieving high-voltage performance and low-temperature power performance. Attached Figure Description

[0017] Figure 1 A process flow diagram of the cathode material preparation method provided in the embodiments of this application.

[0018] Figure 2 The image shows a SEM image (10K magnification) of the cathode material obtained in Example 1.

[0019] Figure 3 The image shows a SEM image (10K magnification) of the cathode material obtained in Example 2.

[0020] Figure 4 The image shows a SEM image (10K magnification) of the cathode material obtained in Comparative Example 1.

[0021] Figure 5 The image shows a SEM image (10K magnification) of the cathode material obtained in Comparative Example 2.

[0022] Figure 6 This is a comparison chart of the discharge capacity of Examples 1-2 and Comparative Examples 1-2.

[0023] Figure 7 The diagram shows a comparison of the low-temperature DCR of Examples 1-2 and Comparative Examples 1-2.

[0024] Figure 8 The images show a comparison of EIS data between Examples 1-2 and Comparative Examples 1-2. Detailed Implementation

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the embodiments of this application pertain. The terminology used herein is for the purpose of describing particular implementations only and is not intended to limit the embodiments of this application. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0026] The following describes some embodiments of this application in detail. Unless otherwise specified, the embodiments and features described below can be combined with each other.

[0027] Existing high-voltage ternary cathode materials cannot simultaneously achieve high-voltage performance, low-temperature power performance, and cycle stability, especially with poor power performance at -10℃.

[0028] For this purpose, please see Figure 1 This application provides a method for preparing a cathode material, comprising the following steps: Step S1: Mix the nickel-cobalt-manganese ternary precursor with lithium salt and dopant, and sinter it once under an oxygen atmosphere to obtain an element-doped matrix. The dopant element in the dopant material includes at least Sr.

[0029] Step S2: Mix the matrix with the first coating material and sinter it in an oxygen atmosphere to form a first coating layer on the surface of the matrix, thereby obtaining a primary coating product. The first coating material includes Ce element.

[0030] Step S3: Mix the primary coating product with the secondary coating material and sinter three times in an air atmosphere to form a secondary coating layer on the surface of the primary coating layer, thereby obtaining the cathode material. The secondary coating material includes Nb and W elements.

[0031] The preparation method provided in this application involves a solid-state reaction in step S1, where a nickel-cobalt-manganese ternary precursor and a lithium salt undergo a solid-state reaction under an oxygen atmosphere via a single sintering process to form a layered crystal matrix. The oxygen atmosphere helps maintain a high valence state for nickel, enhancing the ordered nature of the layered structure. Furthermore, Sr elements enter the crystal lattice of the matrix during sintering, replacing some lithium sites or transition metal sites and causing localized changes in lattice parameters. This change in lattice parameters reduces the lattice constraint on lithium ions along their diffusion paths, facilitating lithium ion migration within the matrix. Simultaneously, the introduction of Sr allows for better crystal growth at relatively low sintering temperatures. The lower sintering temperature also reduces the risk of Ni oxidation, which is easily induced under high-temperature conditions. 2+The migration to lithium sites was effectively controlled, Li + / Ni 2+ The degree of cation mixing decreases accordingly, thereby maintaining the integrity of the matrix's layered structure. Based on this, in step S2, Ce element forms a first coating layer on the matrix surface. This coating layer has multiple beneficial effects: firstly, Ce... 4+ Capable of partially Ni on the substrate surface 2+ Oxidized to Ni 3+ First, the first coating layer optimizes the cation distribution on the substrate surface and further reduces cation mixing. Second, the Ce-O bond has high stability, which helps maintain the structural stability of the cathode material during cycling. Furthermore, the first coating layer reduces side reactions between residual lithium compounds on the substrate surface and the electrolyte, controlling the growth of the CEI film and reducing interfacial impedance. Thus, the first coating layer effectively improves the substrate surface in terms of chemical stability and interfacial optimization. In addition, based on the chemical stabilization and interfacial optimization of the substrate surface by the first coating layer obtained in step S2, Nb and W elements further form a second coating layer on the surface of the first coating layer in step S3. This second coating layer reinforces and modifies the first coating layer, filling any microscopic defects that may exist in the first coating layer, further improving the density and integrity of the coating layer system and enhancing interfacial stability. In summary, this application achieves a balance between high voltage performance, low temperature power performance, and cycle stability of cathode materials through the combined improvement of three levels: bulk diffusion, interface transfer, and structure maintenance. In particular, it can maintain good power performance at a low temperature of -10℃, which can meet the performance requirements of cathode materials for high-power devices.

[0032] In some embodiments, lithium salts are added in the form of lithium hydroxide or lithium carbonate compounds. By selecting lithium salts of the above types, sufficient lithium ions can be provided to participate in the solid-state reaction during sintering, enabling the matrix to form a stable layered crystal structure.

[0033] In some embodiments, Sr is added in the form of strontium carbonate, strontium hydroxide, or strontium oxide compounds. By selecting the above-mentioned types of strontium compounds, Sr ions can be released into the matrix lattice during sintering, achieving bulk doping, thereby adjusting the lattice parameters and optimizing the migration channels of lithium ions in the bulk phase.

[0034] Before step S1, the method further includes: pretreatment of the nickel-cobalt-manganese ternary precursor, the pretreatment steps including: Step 1: Mix the nickel-cobalt-manganese ternary precursor, dispersant, and solvent to obtain a mixture, and then ball-mill the mixture for 4-8 hours to obtain a highly active mixture. This mixing treatment helps to achieve a more uniform distribution of the components in the system, which helps to ensure the homogeneity of the mixture. Through this ball milling treatment, the contact between the components is more sufficient, the activity of the mixture is improved, and it is beneficial to the subsequent processes. The ball milling time can be 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, or any value within the range of any two of the above values.

[0035] In some embodiments, the dispersant in this step includes polyethylene glycol. By selecting a dispersant of the type described above, the agglomeration between precursor particles can be effectively reduced, and the dispersion uniformity of each component in the mixture can be improved.

[0036] In some embodiments, the solvent in this step includes isopropanol. By selecting solvents of the type described above, the components can be adequately wetted and dispersed in the system, providing a suitable liquid medium for ball milling.

[0037] Step 2: Spray dry the mixture at 80℃-100℃ for 2h-4h. Spray drying allows the solvent in the mixture to evaporate rapidly, and the precursor particles maintain a good dispersion state during the drying process, which is beneficial for obtaining a dried product with a relatively uniform particle size distribution. The spray drying temperature can be, for example, 80℃, 85℃, 90℃, 95℃, 100℃, or any value within the range of any two of the above values; the spray drying time can be, for example, 2h, 2.5h, 3h, 3.5h, 4h, or any value within the range of any two of the above values.

[0038] Step 3: Pre-sinter the dried precursor at a temperature of 400℃-600℃ for 3-5 hours. This pretreatment allows for the complete decomposition of organic components in the mixture, initially stabilizing the particle morphology and facilitating crystal structure formation during subsequent sintering. The pre-sintering temperature can be, for example, 400℃, 450℃, 500℃, 550℃, 600℃, or any value within the range of any two of these values. The pre-sintering time can be, for example, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, or any value within the range of any two of these values.

[0039] In some embodiments, when mixing the nickel-cobalt-manganese ternary precursor, lithium salt, Sr element, and dopant element, the amount of Sr element added is 0.01% to 0.05% based on the mass of the nickel-cobalt-manganese ternary precursor. Within this range, Sr element can enter the interior of the matrix lattice, causing a moderate change in the lattice parameters, thereby adjusting the migration channels of lithium ions in the bulk phase and helping to improve the diffusion kinetics of lithium ions in the matrix. The mass ratio of the mixture to Sr element can, for example, be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, or any value within the range of any two of the above values.

[0040] In some embodiments, the doping elements further include Ti and W. Ti and W, acting together as doping elements, can assist in adjusting the lattice structure of the matrix, helping to further stabilize the crystal structure of the matrix, and working synergistically with Sr to enhance the overall structural stability of the matrix.

[0041] In some embodiments, the amount of Ti added is 0.05% to 0.1% based on the mass of the nickel-cobalt-manganese ternary precursor. Within this range, Ti can enter the matrix lattice and play an auxiliary stabilizing role, thereby synergistically enhancing the overall structural stability of the matrix with Sr. The amount of Ti added can be, for example, 0.05%, 0.055%, 0.07%, 0.085%, 0.1%, or any value within the range of any two of the above values.

[0042] In some embodiments, the amount of W added is 0.1% to 0.3% based on the mass of the nickel-cobalt-manganese ternary precursor. Within this range, W can penetrate the matrix lattice and play an auxiliary stabilizing role, thereby synergistically enhancing the overall structural stability of the matrix with Sr. The exemplary amounts of W added can be 0.1%, 0.15%, 0.25%, 0.29%, 0.3%, or any value within the range of any two of the above values.

[0043] In some embodiments, the sintering temperature in step S1 is 800℃-900℃, and the time is 8h-10h. Under these sintering conditions, the matrix can fully crystallize to form the desired crystal structure, and Sr and dopant elements can enter the crystal lattice relatively fully. Simultaneously, this temperature range is beneficial for controlling the degree of cation mixing, maintaining good order in the layered structure of the matrix. Specifically, the addition of Sr lowers the single crystal formation temperature, allowing single crystal particles with a diameter of approximately 1μm-2μm to grow at a sintering temperature of 800℃-900℃. Undoped materials typically require higher temperatures to obtain grains of similar size. Therefore, Sr doping helps to achieve the synthesis of single crystal materials at relatively lower sintering temperatures and reduces the Li-induced defects caused by high-temperature sintering. + / Ni 2+ Cation mixing. The sintering temperature can be, for example, 800°C, 820°C, 840°C, 860°C, 880°C, 900°C or any value within the range of any two of the above values; the sintering time can be, for example, 8h, 8.5h, 9h, 9.5h, 10h or any value within the range of any two of the above values.

[0044] In step S2, the substrate and the first coating material are mixed, and through secondary sintering, Ce combines with oxygen in an oxygen atmosphere to form a first coating layer containing cerium oxide on the substrate surface. This first coating layer plays a dual role in providing physical isolation and chemical stabilization for the substrate surface. On the one hand, after the first coating layer covers the substrate surface, the direct contact area between the substrate surface and the electrolyte is reduced, thereby suppressing interfacial side reactions; on the other hand, Ce... 4+ It has a certain oxidation ability and can oxidize part of the Ni on the substrate surface. 2+ Oxidized to Ni 3+ This optimizes the cation distribution on the substrate surface and further reduces cation mixing. Simultaneously, the high bond energy of the Ce-O bonds in this cerium oxide ensures the first coating layer maintains structural integrity during cycling, thus sustaining the chemical state of the substrate surface over a long period. Furthermore, the first coating layer also confines residual lithium compounds on the substrate surface, limiting their contact with the electrolyte and inhibiting CEI film growth. Consequently, interfacial impedance decreases, and interfacial stability is improved.

[0045] In some embodiments, when the matrix is ​​mixed with the first coating material, the amount of Ce added is 0.01% to 0.05% based on the mass of the matrix. Within this range, Ce can form a relatively uniformly distributed coating layer on the matrix surface, allowing the chemical stabilizing effect of the coating layer on the matrix surface to be fully utilized. The amount of Ce added can be, for example, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, or any value within the range of any two of the above values.

[0046] In some embodiments, the secondary sintering temperature is 600℃~700℃, and the time is 5h~8h. Under these sintering conditions, Ce can form a relatively stable coating layer on the substrate surface, and the coating layer has a relatively tight bond with the substrate. The secondary sintering temperature can, for example, be 600℃, 620℃, 640℃, 660℃, 680℃, 700℃, or any value within the range of any two of the above values; the secondary sintering time can, for example, be 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, or any value within the range of any two of the above values.

[0047] In some embodiments, Ce is added in the form of cerium oxide or cerium nitrate compounds. By selecting the above-mentioned types of cerium compounds, a Ce source can be released during sintering and a uniform and stable coating layer can be formed on the substrate surface.

[0048] In step S3, the substrate undergoes three sintering processes, during which Nb and W elements form a second coating layer on the surface of the first coating layer. This second coating layer further reinforces and modifies the first coating layer. Nb and W elements fill microscopic defects on the surface of the first coating layer, increasing its density. Simultaneously, the high chemical inertness of Nb and W oxides further prevents contact between the electrolyte and the substrate surface, reducing the likelihood of interfacial side reactions. The combined effect of the first and second coating layers enhances the chemical stability and structural integrity of the substrate surface, resulting in overall optimization of the interface state of the cathode material.

[0049] In some embodiments, in step S3, the amount of Nb added is 0.05% to 1% based on the mass of the substrate having the first coating layer. Within this range, the Nb element can be uniformly distributed on the surface of the first coating layer, thereby reinforcing and modifying the first coating layer, and thus improving the density and structural integrity of the coating layer system.

[0050] In some embodiments, in step S3, the amount of W element added is 0.1% to 0.3% based on the mass of the substrate having the first coating layer. Within this range, the W element can work synergistically with the Nb element on the surface of the first coating layer to fill the microscopic defects on the surface of the first coating layer, thereby further improving the density and integrity of the coating layer system and further enhancing the interface stability.

[0051] In some embodiments, the temperature for the three sintering processes is 400℃~600℃, and the time is 4h~6h. Under these sintering conditions, the second coating material can form a structurally stable second coating layer on the surface of the first coating layer, and the bonding between the second coating layer and the first coating layer is relatively tight. Simultaneously, this temperature range allows the Nb and W elements in the second coating material to diffuse sufficiently and be uniformly distributed on the surface of the first coating layer, thereby improving the density and integrity of the coating layer system. The sintering temperature can, for example, be 400℃, 450℃, 500℃, 550℃, 600℃, or any value within the range of any two of the above values; the sintering time can, for example, be 4h, 4.5h, 5h, 5.5h, 6h, or any value within the range of any two of the above values.

[0052] In some embodiments, the cathode material prepared in this application has a single-crystal particle structure, with a median particle size D50 of 1 μm to 5 μm. The single-crystal particle structure results in fewer grain boundaries within the cathode material, allowing for a more unobstructed diffusion path for lithium ions within the particles, which is beneficial for improving the material's rate performance and low-temperature power performance. The median particle size D50 of this cathode material can, for example, be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, or any value within the range of any two of the above values.

[0053] This application also provides a cathode material, which is prepared by the preparation method described above.

[0054] The cathode material was prepared using the aforementioned method. Because this cathode material was prepared using the above method, its matrix is ​​doped with Sr, and its surface is sequentially coated with a first coating layer containing Ce and a second coating layer containing Nb and W. Therefore, the cathode material exhibits improved bulk lithium-ion diffusion kinetics and interfacial charge transfer efficiency. After Sr doping is incorporated into the matrix lattice, it optimizes the migration channels of lithium ions in the bulk phase and reduces Li-C diffusion efficiency. + / Ni 2+ The degree of cation mixing maintains the integrity of the layered structure, thereby enhancing the diffusion kinetics of lithium ions in the bulk phase. Based on this, Ce forms the first coating layer on the substrate surface. 4+ Capable of partially Ni on the substrate surface 2+ Oxidized to Ni 3+This further reduces cation mixing, while the Ce-O bond exhibits high stability, helping to maintain the structural stability of the cathode material during cycling. This coating layer also reduces side reactions between residual lithium compounds on the substrate surface and the electrolyte, controlling the growth of the CEI film and consequently lowering the interfacial impedance. Based on this, Nb and W elements form a second coating layer on the surface of the first coating layer, reinforcing and modifying it, filling any microscopic defects that may exist in the first coating layer, improving its density and integrity, and further enhancing interfacial stability. Through this combination, both the bulk lithium-ion transport efficiency and the interfacial charge transfer efficiency of the cathode material are improved. The improved bulk transport efficiency helps improve the material's capacity and rate performance under high voltage, while the enhanced interfacial stability helps suppress impedance growth and structural degradation caused by side reactions under high voltage. Together, these factors enable the material to maintain relatively stable power output under high voltage conditions. Meanwhile, the improved bulk lithium-ion diffusion kinetics ensures the migration rate of lithium ions within the material at low temperatures, while the reduced interfacial impedance decreases energy loss during charge transfer at low temperatures. These two factors combined enable the material to maintain good power performance even at low temperatures. Furthermore, the stability of the Ce-O bonds and the dense structure of the coating layer enhance the material's resistance to structural degradation, ensuring performance maintenance during long-term use. Therefore, this cathode material can balance high voltage performance, low-temperature power performance, and cycle stability, especially maintaining good power performance at -10℃.

[0055] Specifically, at a high voltage of 4.45V, the first discharge capacity of this cathode material can reach 212.21mAh / g, the coulombic efficiency can reach 92.05%, the 1C capacity is 197.76mAh / g, and the DCR and EIS are effectively improved. It can meet the performance requirements of high-power devices for cathode materials and has broad application prospects in the fields of power batteries and energy storage.

[0056] Compared with related technologies, the preparation method and cathode material provided in this application have the following advantages: 1. The preparation method provided in this application reduces the lattice constraint on lithium ions in the diffusion path by doping Sr elements into the matrix lattice, replacing part of the lithium sites or transition metal sites, thereby helping to improve the diffusion kinetics of lithium ions in the bulk phase of the cathode material under low temperature conditions.

[0057] 2. During the preparation of this cathode material, after Sr elements enter the matrix lattice, the matrix can achieve good crystal growth at a relatively low sintering temperature. This avoids the Ni oxidation that is easily induced under secondary sintering conditions. 2+ The migration to lithium sites was effectively controlled, Li + / Ni 2+ The degree of cation mixing decreases accordingly, thereby maintaining the integrity of the layered structure of the matrix and providing a structural basis for subsequent coating processes.

[0058] 3. In this application, a first coating layer containing Ce and a second coating layer containing Nb and W are sequentially formed on the surface of a substrate. The first coating layer containing Ce can chemically stabilize the substrate surface, reduce side reactions between residual lithium compounds on the surface and the electrolyte, control the growth of the CEI film, and thus reduce the interfacial impedance. Furthermore, the second coating layer containing Nb and W, formed on the surface of the first coating layer, can strengthen and modify the first coating layer, improve the density and integrity of the coating layer system, and further enhance the interfacial stability.

[0059] 4. The cathode material provided in this application has a single-crystal particle structure with fewer internal grain boundaries, resulting in a smooth diffusion path for lithium ions within the particles, which is beneficial for the rapid migration of lithium ions in the bulk phase. Based on this, Sr doping further optimizes the lattice channels, improving the diffusion efficiency of lithium ions; simultaneously, the multilayer coating stabilizes the interface, allowing the interface charge transfer process to proceed smoothly. Through the synergistic effect of Sr doping on the bulk structure, the smooth diffusion path inherent in the single-crystal particle structure, and the stabilizing effect of the multilayer coating on the interface, the cathode material maintains good power performance under both high voltage and low temperature conditions.

[0060] This application also provides a positive electrode sheet, which includes a current collector and a positive electrode active material layer disposed on the surface of the current collector, the positive electrode active material layer comprising the aforementioned positive electrode material. Since this positive electrode sheet comprises the positive electrode material prepared by the above-described method, it can maintain low interfacial impedance and good power performance under high voltage and low temperature conditions, which is beneficial for improving the overall performance of the electrochemical device.

[0061] This application also provides an electrochemical device, including a positive electrode, a negative electrode, and an electrolyte disposed between the positive and negative electrode, wherein the positive electrode is the aforementioned positive electrode. Because this electrochemical device includes the aforementioned positive electrode, the positive electrode material in the positive electrode has good bulk lithium-ion transport efficiency and interfacial charge transfer efficiency. Therefore, this electrochemical device can maintain good power performance under both high voltage and low temperature conditions.

[0062] The present application will be further described below with reference to specific embodiments and comparative examples.

[0063] Example 1 Step 1: Preparation of highly active ternary material precursors: Step 1.1: The ternary precursor Ni of nickel-cobalt-manganese 0.7Co 0.06 Mn 0.24 (OH)2, Zr source (specifically ZrO2), and Al source (specifically Al2O3) were mixed to obtain a mixture. Polyethylene glycol (0.3% of the mixture's weight) and isopropanol (0.3% of the mixture's weight) were added to the mixture, and the mixture was ball-milled for 6 hours to obtain a highly active precursor. The molar ratio of lithium to the total of nickel, cobalt, and manganese was 1.05. Based on the mass of the mixture, the addition amount of Zr was 0.1%, and the addition amount of Al was 0.1%.

[0064] Step 1.2: Spray dry the highly active precursor at 90°C for 3 hours to obtain the dried precursor.

[0065] Step 1.3: Pre-treat the dried precursor in a nitrogen atmosphere at a temperature of 500℃ for 1.5 hours to obtain the pre-treated precursor.

[0066] Step 2: Synthesize ternary cathode single crystal material using a high-temperature solid-state sintering process: Step 2.1: Mix the pretreated precursor with lithium hydroxide, and add an Sr source (specifically SrCO3), a Ti source (specifically TiO2), and a W source (specifically WO3). Perform a single sintering under an oxygen atmosphere at 850℃ for 8 hours to obtain the matrix. Based on the mass of the pretreated precursor, the added Sr element is 0.08%, the added Ti element is 0.05%, and the added W element is 0.1%. The matrix consists of single-crystal particles with a particle size of 1μm~2μm.

[0067] Step 2.2: After cooling the matrix to room temperature, it is pulverized in an air jet mill (pressure 0.25, stage 25) to obtain the matrix after air jet pulverization.

[0068] Step 3: Forming the first coating layer: Step 3.1: Place the air-jet pulverized matrix in a high-speed mixer, add a Co source (specifically Co3O4) and a Ce source (specifically CeO2) for high-speed mixing. Based on the mass of the air-jet pulverized matrix, the amount of Co added is 2% and the amount of Ce added is 0.05%. The high-speed mixing program is to first mix at a low speed of 500 rpm for 5 minutes, and then mix at a high speed of 1000 rpm for 10 minutes.

[0069] Step 3.2: After mixing, a second sintering is performed in an oxygen atmosphere at a temperature of 700°C for 6 hours, so that Ce forms a first coating layer on the surface of the substrate, resulting in a substrate with the first coating layer.

[0070] Step 4: Forming the second coating layer: Step 4.1: The matrix with the first coating layer is subjected to secondary air jet milling (pressure 0.25, fraction 15) in an air jet mill to obtain the secondary air jet milling product. The secondary air jet milling product is placed in a high-speed mixer, and Nb source (specifically Nb(OC2H5)5) and W source (specifically WO3) are added for high-speed mixing. Based on the mass of the secondary air jet milling product, the amount of Nb added is 0.06% and the amount of W added is 0.2%. The mixing program is to first mix at a low speed of 500r for 5min, and then mix at a high speed of 1000r for 10min.

[0071] Step 4.2: The high-speed mixed product obtained in step 4.1 is sintered three times in air atmosphere. The sintering temperature is 500℃ and the time is 5 hours, so that Nb and W form a second coating layer on the surface of the first coating layer, and the cathode material is obtained.

[0072] Step 4.3: Pass the cathode material through a 300-mesh sieve to obtain a single-crystal ternary cathode material with a particle size of 2μm.

[0073] Example 2 The difference from Example 1 is that in step 3.1, the amount of Ce added is 0.15% based on the mass of the matrix after air jet pulverization, while the rest of the preparation method is the same as in Example 1.

[0074] Comparative Example 1 The difference from Example 1 is that no Sr source was added in step 2.1, while the rest of the preparation method is the same as in Example 1.

[0075] Comparative Example 2 The difference from Example 1 is that Ce was not added in step 3.1, while Co was added in the same amount as in Example 1. That is, only Co was added in step 3.1, and Ce was not added. The rest of the preparation method was the same as in Example 1.

[0076] Comparative Example 3 The difference from Example 1 is that Nb and W coating was not performed, i.e., steps 4.1 to 4.3 were omitted. The remaining preparation methods are consistent with Example 1. Cathode material performance testing: Particle size testing: Malvern laser particle size analyzer (3000).

[0077] SEM morphology observation: Thermo Fisher Scientific scanning electron microscope, accelerating voltage 10kV, magnification 1k.

[0078] Electrochemical performance tests can only be conducted after the cathode material has been assembled into a coin cell.

[0079] Preparation of coin cell half-cells: The assembly of coin cell half-cells was carried out in a glove box where the water and oxygen content were both less than 1 ppm. A CR2025 coin cell casing was used, and the assembly sequence was as follows: a lithium metal sheet was used as the counter electrode (negative electrode), a porous membrane was used as the separator, and 1.0 M LiPF6 was dissolved in a mixed solvent of ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1 as the electrolyte. During assembly, the spring and gasket are placed sequentially into the negative electrode shell, the lithium sheet is placed in the center of the gasket and pressed firmly, and 25μL of electrolyte is dropped onto the surface of the lithium sheet; then the separator is covered, and another 25μL of electrolyte is dropped onto the separator to fully wet it; then the punched positive electrode sheet is placed in the center of the separator; finally, the positive electrode shell is covered and placed in a coin cell sealing machine to obtain a coin cell half-cell. The coin cell half-cell, after being left to stand, is placed on the Blue Battery testing system for constant current charge-discharge testing. The operating voltage range for the first discharge capacity test is 2.8V~4.45V, the charge-discharge rate is +1C / -1C, and the CV cutoff current is 0.01C.

[0080] The operating voltage range for high-temperature cycling testing is 2.8V~4.45V, the test temperature is 45℃, and the charge / discharge rate is +1C / 1C.

[0081] Initial coulombic efficiency (%) = (initial discharge specific capacity / initial charge specific capacity) × 100%.

[0082] Rate performance: At 25℃, the battery was charged at a constant current of 0.1C to 4.45V, and then charged at a constant voltage of 4.45V until the current dropped to 0.05C. After standing for 10 minutes, it was discharged at constant currents of 0.1C, 0.5C and 1C to 2.8V. The discharge specific capacity at each rate was recorded, and the rate performance retention rate was calculated. The 1C / 0.1C capacity retention rate (%) = (1C discharge specific capacity / 0.1C discharge specific capacity) × 100%.

[0083] Low-temperature DC internal resistance (DCR) test: At -10℃, the battery is charged at a constant current of 0.1C to 4.45V, then charged at a constant voltage of 4.45V until the current drops to 0.05C. After resting, it is discharged at a constant current of 1C for 10s. The voltage before discharge and the voltage after discharge are recorded, and the DC internal resistance is calculated, where DCR (Ω) = (voltage before discharge - voltage after discharge) / discharge current.

[0084] Low-temperature 15mW constant power discharge time: At -10℃, the battery was charged at a constant current of 0.1C to 4.45V, then charged at a constant voltage of 4.45V until the current dropped to 0.05C. After standing for 10 minutes, it was discharged at a constant power of 15mW, and the voltage was discharged from 4.45V to 2.8V. The discharge time was recorded.

[0085] Electrochemical impedance spectroscopy (EIS) test: At 25°C, the battery was charged at a constant current of 0.1C to 4.45V, then charged at a constant voltage of 4.45V until the current dropped to 0.05C, bringing the battery to 100% SOC. After resting for 3 hours, the battery was tested using an electrochemical workstation with a frequency range of 100kHz to 0.01kHz and an amplitude of 5mV. Since the wiring harness has its own shielding, no additional shielding box was used.

[0086] The experimental test results of Examples 1 to 2 and Comparative Examples 1 to 3 are shown in Table 1 below.

[0087] Table 1 Results Analysis: Figures 2 to 5 The SEM images show that the primary particle distribution of the material obtained in Example 1 is relatively uniform, and the particle surface is relatively smooth. The morphology of Example 2 is basically the same as that of Example 1, indicating that the increase in Ce coating amount has no significant impact on the primary particle morphology. Comparative Example 1, without Sr doping, has slightly larger primary particle size and a wider particle size distribution range, reflecting that Sr doping helps to achieve uniform grain growth at a relatively low sintering temperature and suppresses excessive particle growth. Comparative Example 2, without Ce coating, has a particle morphology that is not significantly different from that of Example 1, indicating that Ce coating has little impact on the primary particle morphology of the matrix.

[0088] Depend on Figure 6 As shown in the discharge capacity comparison chart, Example 1 exhibits the highest discharge capacity among all samples. Comparative Example 1, without Sr doping, has a lower discharge capacity than Example 1, reflecting that Sr doping helps improve the lithium-ion transport efficiency in the bulk phase. Comparative Example 2, without Ce coating, also has a lower discharge capacity than Example 1, indicating that Ce coating has a positive effect on the material's capacity. In Example 2, increasing the Ce coating to 0.15% slightly alters the discharge capacity compared to Example 1, but the increased coating thickness positively impacts interface stability. Therefore, the synergistic effect of Sr doping and Ce coating in these examples results in better capacity performance.

[0089] Depend on Figure 7 The low-temperature DCR comparison charts show that the DCR values ​​of Examples 1 and 2 are lower than those of Comparative Examples 1 and 2, indicating that the combined effect of Sr doping and Ce coating helps to reduce the DC internal resistance of the material under low-temperature conditions and improve power performance. Comparative Example 1, without Sr doping, has a higher DCR value, indicating that the lack of Sr doping hinders the diffusion of lithium ions in the bulk phase, leading to increased low-temperature internal resistance. Comparative Example 2, without Ce coating, also has a higher DCR value than Example 1, indicating that Ce coating plays an important role in reducing interfacial impedance.

[0090] Depend on Figure 8 The EIS comparison charts show that the interface impedance of Examples 1 and 2 is lower than that of Comparative Examples 1 and 2. Comparative Example 1, due to the lack of Sr doping, has a higher Li content in its bulk structure. + / Ni 2+ The high degree of cation mixing leads to increased lithium-ion transport impedance. In Comparative Example 2, due to the lack of Ce coating, the residual lithium compounds on the substrate surface were not effectively treated, resulting in more significant CEI film growth and increased interfacial charge transfer impedance. In contrast, Example 1 combines the optimization effect of Sr doping on the bulk structure with the stabilizing effect of Ce coating on the interface, thus exhibiting the lowest interfacial impedance and the highest charge transfer efficiency.

[0091] In summary, Sr doping helps optimize the bulk structure of the matrix, promotes uniform grain growth, and reduces Li content. + / Ni 2+ The mixed arrangement of cations improves the diffusion kinetics of lithium ions in the bulk phase under low-temperature conditions; Ce coating helps stabilize the substrate surface, reduces side reactions between residual lithium compounds and the electrolyte, inhibits excessive growth of the CEI film, and lowers interfacial impedance. The synergistic effect of these two factors enables Example 1 to maintain low DCR and EIS and good power performance under both high voltage and low temperature conditions. Example 2 further enhances the interfacial stabilization effect by increasing the Ce coating amount. Comparative Examples 1 and 2, lacking Sr doping or Ce coating respectively, have certain deficiencies in bulk diffusion or interfacial transport, and their overall performance is inferior to Examples 1 and 2.

[0092] In summary, this application improves both the bulk lithium-ion diffusion kinetics and interfacial charge transfer efficiency of the material by doping Sr into the matrix lattice, combined with a multilayer coating structure containing a Ce first coating layer and a Nb and W second coating layer. Sr doping helps optimize lattice channels and reduce cation mixing, Ce coating helps stabilize the matrix surface and reduce interfacial impedance, and Nb and W coating further enhance the density and structural integrity of the coating system. The synergistic effect of these three elements enables the cathode material to maintain good power performance under both high voltage and low temperature conditions.

[0093] The above description describes some specific embodiments of this application, but in actual applications, the application should not be limited to these embodiments. For those skilled in the art, other modifications and alterations made based on the technical concept of this application should fall within the protection scope of this application.

Claims

1. A method for preparing a positive electrode material, characterized in that, include: A nickel-cobalt-manganese ternary precursor is mixed with lithium salt and dopant material, and sintered once under an oxygen atmosphere to obtain an element-doped matrix. The doping element in the dopant material includes at least Sr. The matrix is ​​mixed with a first coating material, and then sintered again in an oxygen atmosphere to form a first coating layer on the surface of the matrix, yielding a primary coating product. The first coating material includes Ce element; and... The primary coating product is mixed with the second coating material and sintered three times in an air atmosphere to form a second coating layer on the surface of the first coating layer, thereby obtaining the cathode material. The second coating material includes Nb and W elements.

2. The preparation method according to claim 1, characterized in that, In the step of mixing the nickel-cobalt-manganese ternary precursor, lithium salt, and dopant, the amount of Sr added is 0.01%~0.05% based on the mass of the nickel-cobalt-manganese ternary precursor; and / or, When the matrix is ​​mixed with the first coating material, the amount of Ce added is 0.01% to 0.05% based on the mass of the matrix.

3. The preparation method according to claim 1, characterized in that, The sintering temperature is 800℃-900℃ and the time is 8h~10h. The matrix is ​​a single crystal particle with a particle size of 1μm~2μm.

4. The preparation method according to claim 1, characterized in that, Prior to the step of mixing the nickel-cobalt-manganese ternary precursor with lithium salt and dopant, the method further includes: pretreating the nickel-cobalt-manganese ternary precursor, the pretreating step including: The untreated nickel-cobalt-manganese ternary precursor, dispersant, and solvent were mixed to obtain a mixture; The mixture was spray-dried at 80℃-100℃ for 2-4 hours to obtain the dried precursor; and The dried precursor is pre-sintered at a temperature of 400℃-600℃ for 3-5 hours.

5. The preparation method according to claim 1, characterized in that, In the step of mixing the nickel-cobalt-manganese ternary precursor, lithium salt and dopant material, based on the mass of the nickel-cobalt-manganese ternary precursor, the amount of dopant elements other than Sr added to the dopant material is 0.05%~0.1%.

6. The preparation method according to claim 1, characterized in that, The doping elements also include Ti and W.

7. The preparation method according to claim 6, characterized in that, Based on the mass of the nickel-cobalt-manganese ternary precursor, the amount of Ti added is 0.05%~0.1%; Based on the mass of the nickel-cobalt-manganese ternary precursor, the amount of W added is 0.1% to 0.3%.

8. The preparation method according to claim 1, characterized in that, The secondary sintering temperature is 600℃~700℃, and the time is 5h~8h; and / or, The temperature for the three sintering processes is 400℃-600℃, and the time is 4h-6h.

9. A positive electrode material, characterized in that, The cathode material is prepared by the preparation method according to any one of claims 1 to 7.

10. An electrochemical device, characterized in that, It includes a positive electrode, a negative electrode, and an electrolyte disposed between the positive electrode and the negative electrode, wherein the positive electrode is the positive electrode material as described in claim 9.